Annulling a dangerous liaison: vaccination strategies against AIDS and tuberculosis. - Kaufmann, S; Mcmichael, A (2005)
Human immunodeficiency virus (HIV) and Mycobacterium tuberculosis annually cause 3 million and 2 million deaths, respectively. Last year, 600,000 individuals, doubly infected with HIV and M. tuberculosis, died. Since World War I, approximately 150 million people have succumbed to these two infections--more total deaths than in all wars in the last 2,000 years. Although the perceived threats of new infections such as SARS, new variant Creutzfeldt-Jakob disease and anthrax are real, these outbreaks have caused less than 1,000 deaths globally, a death toll AIDS and tuberculosis exact every 2 h. In 2003, 40 million people were infected with HIV, 2 billion with M. tuberculosis, and 15 million with both. Last year, 5 million and 50 million were newly infected with HIV or M. tuberculosis, respectively, with 2 million new double infections. Better control measures are urgently needed.